Balance sheet of soil nutrients as influenced by soil fertility levels in different varieties of aerobic rice (Oryza sativa L.) - KUMAR, SANDEEP; KOUR, SARABDEEP; GUPTA, MEENAKSHI; CHOUDHARY, KARTIKEYA (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted at the Research Farm of Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu to evaluate the effect of different varieties and fertility levels on yield, nutrient uptake and balance sheet of nutrients in rice under aerobic environment. The experiment was conducted in factorial Randomized block design including four varieties viz. PR-115, DRRH-3, PAC- 837 and PR-121 and four fertility levels viz. Control (N0: P0: K0), N90: P45: K22.5, N120: P60: K30 and N150: P75: K37.5 kg ha-1. The results revealed that the rice variety PAC-837 recorded highest grain yield, straw yield and harvest index followed by variety DRRH-3 and lowest grain and straw yield was recorded in indigenous variety PR-121. The grain yield increase in PAC-837 was significantly superior over all other varieties. Hybrids found to be more prominent under aerobic conditions as compared to inbreds, also recorded higher nutrient response. Highest fertility level (N150: P75: K37.5 kg ha-1) recorded higher grain and straw yield which was significantly superior to all other fertility levels, whereas fertility level of 120:60:30 kg N-P2O5-K2O ha 1 recorded highest nutrient response. Nutrient uptake (NPK) was also recorded highest in variety PAC-837 which was at par with DRRH-3 but significantly superior to PR-121 and PR- 115. Highest fertility level (N150: P75: K37.5 kg ha-1) recorded highest uptake of nutrients though it was at par with 120:60:30 kg N-P2O5-K2O ha 1. Negative soil nutrient balance was recorded in hybrids due to their higher nutrient demand and uptake whereas highest fertility level recorded a positive nutrient balance.